Implementasi Metode Bernyanyi Dalam Pembelajaran Fiqih Di Pesantren Miftahul Jannah An-Nuriyyah - Azzahra, Aura Aulia; Syahidin, Syahidin; Budiyanti, Nurti (Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 2024)
Learning in pesantren with conventional methods is often faced with challenges in the learning process. The application of innovative learning methods is needed so that the learning process becomes more interesting and effective for students. This study aims to explore the implementation of the singing method in fiqh learning at Miftahul Jannah An-Nuriyyah Islamic Boarding School. The research approach used is qualitative with descriptive methods. Data collection techniques are direct observation, interviews, and documentation. The research subjects consisted of teachers and students in the pesantren. The results showed that the singing method was able to increase santri involvement in the learning process and help them get the material more easily and fun. This method also creates a dynamic learning atmosphere and makes it easier for santri to memorize and understand fiqh concepts. The main challenge in applying this method is the creativity for teachers in composing fiqh material into the form of song lyrics so that it is easier to understand and in accordance with the core of the material. The conclusion of this study is that the singing method can be an effective alternative in learning fiqh in pesantren, especially in improving students' understanding and memory of the material taught.